Mulching as a weed management tool in container plant production - review - Khamare, Yuvraj; Marble, S. Christopher (Frontiers in Agronomy, 2023)
Weed management in container plant production is a serious problem and remains one of the most expensive and time-consuming aspects of the industry. Weeds cause severe reductions in crop growth due to the limited growing environment characteristic of container plant production. The container nursery industry relies heavily on a limited number of preemergence herbicide options. The use of herbicides as the primary means to manage weeds has resulted in some negative consequences such as high chemical costs, leaching, runoff, and concerns with recycling irrigation water. Additionally, nursery growers are shifting their focus towards different nonchemical weed management strategies because many ornamental plants are very sensitive to preemergence herbicides. One such method is using organic mulch to control weeds in container plant production. Mulching is the foundation of a nonchemical weed management protocol and acts as the first line of defense against weeds. Organic mulches used in container plant production include rice hulls, pine bark, wood chips, wood shavings, coconut coir, nut (peanut, pecan) shells, oyster shells, cacao bean hulls, pelletized newspaper, recycled newspaper, pine straw, and other materials; material selection often depends on the availability of the product. The objective of this manuscript is to provide a comprehensive review of existing research on the utilization of various mulch materials as a weed management tool in container plant production. Additionally, it aims to highlight any critical knowledge gaps and provide suggestions for possible future research.